Modulation of Nitro-fatty acid signaling: prostaglandin reductase-1 is a Nitroalkene reductase - Vitturi, Dario A. (2013)
Background: Nitroalkenes are electrophilic anti-inflammatory mediators that signal via Michael addition and are metabolized in vivo. Results: Prostaglandin reductase-1 is identified as a nitroalkene reductase. Conclusion: Prostaglandin reductase-1 reduces fatty acid nitroalkenes to nitroalkanes, inactivating electrophilic reactivity. Significance: A mammalian enzyme is identified that metabolizes fatty acid nitroalkenes in vivo to silence their signaling reactions.